(untitled) (International relations and international law Journal, 2018)
The article deals with the establishment and upgrading of information systems in the activities of the custom authorities in Kazakhstan in connection with the measures arising from the Plan of the Nation «100 concrete steps» put forward by the Head of State Nursultan Nazarbayev in March 2015, as the nation’s plan of entering the 30 developed countries in the world, studied scientific and organizational issues related to the improvement of the activities of numerous participants of foreign economic activity, the steps of formation of information systems that create certain conditions in order to reduce the risk of corruption in customs. The emphasis that today informatization practically avoided movement process, to be exact – export through frontier of Kazakhstan of cultural values is placed. It is a gap not only process of informatization of customs service, but also a gap in the legislation of the Republic of Kazakhstan. Authors on the basis of the analysis of big theoretical and practical material make recommendations about their improvement. Key words: information system, customs authorities, electronic customs, corruption, cultural values.